2004
DOI: 10.1099/mic.0.26888-0
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analysis of Streptococcus mutans metabolic phenotype during acid tolerance

Abstract: Two-dimensional gel electrophoretic analysis of the proteome of Streptococcus mutans grown at a steady state in a glucose-limited anaerobic continuous culture revealed a number of proteins that were differentially expressed when the growth pH was lowered from pH 7?0 to pH 5?0. Changes in the expression of metabolic proteins were generally limited to three biochemical pathways: glycolysis, alternative acid production and branched-chain amino acid biosynthesis. The relative level of expression of protein spots r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
134
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(152 citation statements)
references
References 56 publications
14
134
4
Order By: Relevance
“…Notwithstanding, neither this nor previous 2-DGE analyses (Len et al, 2003(Len et al, , 2004b have identified the integral cytoplasmic membrane glucose transporters EII man and EII glc , or the glucose permease of S. mutans required for uptake of glucose (Cvitkovitch et al, 1995;Vadeboncoeur et al, 1991) due to their hydrophobic structure. As a consequence, any change that the level of expression of these transporters may have on glucose uptake and subsequent metabolic rate cannot be surmised.…”
Section: D Displays Of Fractionated Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding, neither this nor previous 2-DGE analyses (Len et al, 2003(Len et al, , 2004b have identified the integral cytoplasmic membrane glucose transporters EII man and EII glc , or the glucose permease of S. mutans required for uptake of glucose (Cvitkovitch et al, 1995;Vadeboncoeur et al, 1991) due to their hydrophobic structure. As a consequence, any change that the level of expression of these transporters may have on glucose uptake and subsequent metabolic rate cannot be surmised.…”
Section: D Displays Of Fractionated Proteinsmentioning
confidence: 99%
“…Alterations in the fermentation phenotype of the S. mutans biofilm It is logical to hypothesize that any slowing of the growth rate in mature biofilms might be reflected in a down-turn in the level of metabolic enzymes, even though care should be taken in interpreting such a reduction as implying a corresponding down-turn in the flux of metabolites (Len et al, 2004b). Notwithstanding, neither this nor previous 2-DGE analyses (Len et al, 2003(Len et al, , 2004b have identified the integral cytoplasmic membrane glucose transporters EII man and EII glc , or the glucose permease of S. mutans required for uptake of glucose (Cvitkovitch et al, 1995;Vadeboncoeur et al, 1991) due to their hydrophobic structure.…”
Section: D Displays Of Fractionated Proteinsmentioning
confidence: 99%
“…The dysfunction of AdhE may cause shunting of pyruvate towards the production of formate. Formic acid is a strong acid, which may contribute to a greater production of intracellular H + (Len et al, 2004). This possible internal acidification may create a severe stress signal leading to the abrogation of mutacin production.…”
Section: Genes Involved In Energy Metabolismmentioning
confidence: 99%
“…CiaH is the histidine kinase of a two-component signal-transduction system, CiaH/R (Giammarinaro et al, 1999;Zähner et al, 2002), while LuxS is responsible for the synthesis of the interspecies cell signalling molecule autoinducer 2 (AI-2) (Schauder et al, 2001;Xavier & Bassler, 2003). In addition to regulating mutacin I production, both CiaH and LuxS were also found to be involved in regulating other cellular functions in S. mutans such as biofilm formation and stress tolerance (Len et al, 2004;Merritt et al, 2003;Qi et al, 2004). As a preliminary attempt to understand the control of mutacin I The pZero-2 cloning vector (Invitrogen) was used to facilitate library construction in E. coli, and as a suicide vector in S. mutans.…”
Section: Introductionmentioning
confidence: 99%
“…By the appropriate use of the acetate and ethanol branches of the PFL pathway, S. mutans can readily adjust NADH oxidation to the actual need. Without further anabolic diversion of the fi nal products, the amount of formic acid produced by glycolysis is equivalent to the total amount of acetic acid and ethanol 6 . An important characteristic which distinguishes S. mutans from other oral streptococci is its ability to ferment sugar alcohols such as sorbitol, and mannitol.…”
Section: Introductionmentioning
confidence: 99%